Charles Buford papers - Buford, Charles, 1797-1866.; Duke, James W.
Chiefly family and personal correspondence commenting on political and social conditions prior to and during the Civil War, particularly slavery and its abolition and the effects of the war on civilians. Includes a letter from James W. Duke, a Confederate soldier in the Union prison at Rock Island, Ill.; a satirical essay by Buford on the slavery question; and a biographical sketch of Buford. Other correspondents include T.H. Bradford, John C. Breckinridge, James F. Buckner, W.N. Budd, Garrett Davis, N.W. Duke, J. Henry (John Flournoy Henry), and George S. Williams.
In part, typewritten transcripts.
Planter of Georgetown, Ky. Moved to Rock Island, Ill., circa 1853.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Bradford, T. H. -- Correspondence; Breckinridge, John C. -- 1821-1875 -- Correspondence; Buckner, James F. -- Correspondence; Budd, W. N. -- Correspondence; Davis, Garrett, -- 1801-1872 -- Correspondence; Duke, N. W. -- Correspondence; Henry, J. -- 1793-1873 -- Correspondence; Williams, George S., -- active 1863 -- Correspondence; Slavery -- United States; Illinois -- History -- Civil War, 1861-1865.; Georgetown (Ky.) -- History; Kentucky -- History -- Civil War, 1861-1865.; Rock Island (Ill.) -- History; United States -- History -- Civil War, 1861-1865 -- Prisoners and prisons; United States -- Politics and government -- 1845-1861.; United States -- Politics and government -- 1861-1865.; United States -- Social conditions -- To 1865.; Plantation owners